2003
DOI: 10.1093/sleep/26.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cost of Home-Initiated Auto-nCPAP versus Conventional nCPAP

Abstract: Treatment of OSAS with auto-nCPAP initiated at home is effective and reliable and reduces the time from diagnosis to therapy and the cost of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 14 publications
5
51
0
1
Order By: Relevance
“…This finding is consistent with previous findings in adults 5,11 and the AASM practice parameters from 2007. 12 Although the AutoMean was on average 2.6 cm H 2 O below the treatment pressure recommended following a manual CPAP titration PSG (PSG pressure), the Auto90 was on average within 1 cm H 2 O of the recommended treatment pressure derived from manual titration (PSG pressure).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous findings in adults 5,11 and the AASM practice parameters from 2007. 12 Although the AutoMean was on average 2.6 cm H 2 O below the treatment pressure recommended following a manual CPAP titration PSG (PSG pressure), the Auto90 was on average within 1 cm H 2 O of the recommended treatment pressure derived from manual titration (PSG pressure).…”
Section: Discussionsupporting
confidence: 93%
“…Although in some reports significant differences were found, they were small in absolute terms. Besides, sleepiness, as evaluated by the Epworth sleepiness scale, was reduced by all A-CPAP devices as much as by F-CPAP [33,[41][42][43][44][48][49][50]. These findings suggest that differences in delivered pressures are not paralleled by differences in efficacy in correcting patients' SDB.…”
Section: Do Different A-cpap Devices Perform Equally?mentioning
confidence: 76%
“…However, despite differences in pressure output the effects on polysomnographic variables prove to be similar for most A-CPAP devices. All of the published reports demonstrate effectiveness in reducing, and usually normalising, obstructive respiratory disorders and sleep fragmentation [11,[33][34][35][37][38][39][40][41][42][43][44][45][46][47]. Although in some reports significant differences were found, they were small in absolute terms.…”
Section: Do Different A-cpap Devices Perform Equally?mentioning
confidence: 99%
“…In the study by d'Ortho et al (33), 15 responders (60%) preferred APAP, eight preferred CPAP and two opted for surgery. Planes et al (29) reported that a large majority of patients in both a conventional CPAP group and an APAP group were satisfied with their treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…Only one study (29) was located that included comparative cost information. In that study, APAP treatment was started at home for one group of patients.…”
Section: Costsmentioning
confidence: 99%